Relationship between anxiety and mental toughness among UAAP track and field student-athletes - Tagayun, Shiela Mae A. 2000-; Kho, Edward P. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
This study explores the correlation between anxiety and mental toughness among track and field student-athletes participating in the University Athletic Association of the Philippines (UAAP). Track and field, a multidisciplinary sport, requires a blend of physical strength, strategic thinking, and ability to perform under pressure is needed for track and field sports. Utilizing a correlational research design, data were collected from 40 track and field student-athletes, representing all eight UAAP universities, using the Sport Anxiety Scale (SAS) and the Mental Toughness Test (MTT). Results indicated a moderate positive correlation between anxiety and mental toughness, suggesting that higher anxiety levels are associated with higher mental toughness. However, anxiety negatively correlated with commitment but positively correlated with concentration, control under pressure, and confidence. Additionally, mental toughness showed the strongest positive correlation with worry, a sub-scale of anxiety. These findings challenge the conventional understanding of the relationship between anxiety and mental toughness, highlighting the nuanced role of anxiety in enhancing certain aspects of mental toughness. The study's insights can be utilized to develop targeted strategies for improving the psychological resilience and performance of student-athletes
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Anxiety; Track and field athletes; Sports -- Psychological aspects